Effect of planting distance and fertilizer combination on growth and production of Upland Rive line UNHZ 12 - Asfaruddin Asfaruddin; Prihanani Prihanani; Eko Wahyudi (University of Prof. Dr. Hazairin, SH, 2022)
The purpose of this study was to determine the distance and combination of fertilizers, and their interactions on the growth and yield of lowland rice. The design used is a split plot design. The main plot is the Planting Distance (J) which consists of 3 levels, namely: J1 : Conventional 20 x 20 cm, J2 : Jajar legowo 25 x 25 cm, J3 : Jajar legowo 30 x 30 cm. As a sub-plot is a combination of Petroganik (P ) fertilizer, Phonska, and urea which consists of 3 levels, namely, P1 : Combination of Petronic, Phonska and Urea fertilizers with a ratio of 3: 3: 2, P2 : Combination of Petronik, Phonska and Urea fertilizers with ratio 2 : 1 : 1, and P3 : Combination of Petronik, Phonska and Urea fertilizers with a ratio of 5 : 2 : 1. The results showed that plant spacing had no significant effect on plant height 30, 45, 60 and 75 DAP, the total number of tillers was 15 , 30, and 45 DAP, flowering age, harvest age, number of grain per panicle, production weight per plot and weight of 100 grains. Significant effect on the number of tillers aged 60 days, the number of tillers aged 75 days and clumped weight. The best spacing is 25 cm x 25 cm. The combination of fertilizers had a significant effect on the number of tillers aged 70 days, but had no significant effect on the other variables. The interaction of the combination of fertilizer and plant spacing gave a significant effect on the total number of tillers at 30 DAP, but had no significant effect on the other variables. The best results were obtained at a spacing of 25 cm x 25 cm with a combination of Petronik, Phonska and Urea fertilization with a ratio of 5: 2: 1